Analisis Keterampilan Menulis Paragraf Siswa Kelas Sepuluh di SMA Negeri 1 Kuok - Wira Elvina (FKIP - Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze paragraph writing skills of tenth-grade students at SMA Negeri 1 Kuok. It applied a qualitative approach using writing tests and documentation as instruments. The sample consisted of 20 students selected by purposive sampling. Assessment was based on five writing components: content, organization, vocabulary, grammar, and mechanics. The findings showed that the average student score was 78.2, which falls into the